The Guarantee of Contract Stability Based on a Renegotiation Clause - Hani Mounes Awad; Asmaa Saad Elhadedy; Ali Mohamed Altaly (Journal of Legal Sciences, 2024)
The study dealt with one of the most important means of achieving stability in the contractual legal centers of international trade contracts, namely renegotiation, and the importance of this means of reviewing contracts is reflected in many considerations, the most important of which are considerations of justice, if the principle of the contract Sharia law is considered the most important sources of contract strength as a source of, in addition Despite the fact that it is just one of the clauses of the contract, until its activation and entry into force requires the concerted efforts of the parties to the contract, as well as the legal effects arising from the implementation of the renegotiation clause, whether negotiations succeed or negotiations fail, and the subject was addressed through the descriptive analytical approach, where the descriptive approach was used about those negotiations it is an obligation to take care, with The study recommended several recommendations, including emphasizing the importance of including the renegotiation clause in futures contracts, and the need to formulate the renegotiation clause in two ways, first is a general one that addresses all events that may interfere with implementation and constitute an island change in the implementation process, and the second is to identify specific facts for renegotiation.